A comprehensive parametric, energy and exergy analysis of a novel physical energy storage system based on carbon dioxide Brayton cycle, low-temperature thermal storage, and cold energy storage. (15th December 2020) - Zhang, Yuan; Liang, Tianyang; Tian, Zhen; Gao, Wenzhong; Yang, Ke
Highlights: A novel energy storage system based on carbon dioxide Brayton cycle is proposed. Low-temperature thermal storage and cold energy storage are adopted in the system. The storage of thermal energy and cold energy can meet the demand for utilization. There exists an optimal pressure ratio to maximize power and exergy efficiencies. In heat exchangers, heat exchanger3 should be given priority for better performance. Abstract: Low-temperature energy storage system is an important development direction of physical energy storage technology, which can avoid the technical difficulties caused by high-temperature conditions. In this paper, a novel physical energy storage system based on carbon dioxide Brayton cycle, low-temperature thermal storage, and cold energy storage was proposed. Water was chosen as the working medium for thermal storage, and ice slurry was chosen as the working medium for cold energy storage. The working processes of this low-temperature carbon dioxide energy storage system were introduced in detail and the corresponding thermodynamic model was established. In addition to the evaluation based on power efficiency and exergy efficiency, thermal energy utilization efficiency and cold energy utilization efficiency were defined to assess the feasibility of the independent operation of the system. Parametric analysis was carried out to analyze the effects of several important parameters on system performance. The results showed that, for the system under the basic working condition, power efficiency was 55.7%, exergy efficiency was 52.87%, thermal energy utilization efficiency was 83.3% and cold energy utilization efficiency was 89.5%. The total exergy destruction was 48.07 kW and the largest exergy destruction came from the compressor. According to the sensitivity analysis, in turbomachinery, turbine efficiency had the greatest influence on power efficiency as well as exergy efficiency, and when turbine efficiency increased by 1%, both power efficiency and exergy efficiency increased by 0.634%. There was an optimum for pressure ratio to get the maximum values of power efficiency and exergy efficiency, and the optimum was 6.5. The decrease of the pressure drop in heat exchangers could increase power efficiency and exergy efficiency whereas the decrease of minimum temperature difference in heat exchangers could increase the four efficiencies. Measured in terms of the degree of influence, heat exchanger3 had the greatest influence and should be paid more attention. As to the cooling medium, the increase of the inlet temperature of water could increase power efficiency and exergy efficiency. Besides, there was an optimum for the mass flow rate of water to maximize power efficiency and exergy efficiency. Finally, it should be noted that, to ensure that the storage of cold energy during the charge process could meet the demand of cold energy during the discharge process, all the parameters studied needed to be carefully set. Relevant research provided important guidance for understanding the thermodynamic performance of the low-temperature energy storage system with carbon dioxide as the working fluid.